CONNECTION OF INTERPERSONAL RELATIONS AND VALUE ORIENTATIONS OF ADOLESCENTS IN A SEMI-CLOSED EDUCATIONAL GROUP - Tarasov, S.V.; Drobysheva , T.V. (Modern Psychology, 2019)
The article is devoted to the problem of determination interpersonal relations of adolescents in semi-closed study group. The paper highlights the signs of a semi-closed study group, describes the specifics of students’ activity in such a group. The results of the pilot study are given. His goal was to identify the relationship between value orientations and interpersonal relations of adolescents studying in a semi-closed study group. Two groups of students from the cadet corps (semi-closed study groups) took part in the work. The results of the relationship of the respondents’ value orientations and their orientation in interpersonal relations with peers are presented. It is shown that the orientation of adolescents to restraint, self-control (volitional, emotional) in relations with peers, distinguishing them from peers from general education schools (open groups) is due to the system of value orientations formed by the current period of development.